Why drug exposure is frequently associated with T-cell mediated cutaneous hypersensitivity reactions - Line, James; Saville, Eleanor; Meng, Xiaoli; Naisbitt, Dean (Frontiers in Toxicology, 2023)
Cutaneous hypersensitivity reactions represent the most common manifestation of drug allergy seen in the clinic, with 25% of all adverse drug reactions appearing in the skin. The severity of cutaneous eruptions can vastly differ depending on the cellular mechanisms involved from a minor, self-resolving maculopapular rash to major, life-threatening pathologies such as the T-cell mediated bullous eruptions, i.e., Stevens Johnson syndrome/toxic epidermal necrolysis. It remains a significant question as to why these reactions are so frequently associated with the skin and what factors polarise these reactions towards more serious disease states. The barrier function which the skin performs means it is constantly subject to a barrage of danger signals, creating an environment that favors elicitation. Therefore, a critical question is what drives the expansion of cutaneous lymphocyte antigen positive, skin homing, T-cell sub-populations in draining lymph nodes. One answer could be the heterologous immunity hypothesis whereby tissue resident memory T-cells that express T-cell receptors (TCRs) for pathogen derived antigens cross-react with drug antigen. A significant amount of research has been conducted on skin immunity in the context of contact allergy and the role of tissue specific antigen presenting cells in presenting drug antigen to T-cells, but it is unclear how this relates to epitopes derived from circulation. Studies have shown that the skin is a metabolically active organ, capable of generating reactive drug metabolites. However, we know that drug antigens are displayed systemically so what factors permit tolerance in one part of the body, but reactivity in the skin. Most adverse drug reactions are mild, and skin eruptions tend to be visible to the patient, whereas minor organ injury such as transient transaminase elevation is often not apparent. Systemic hypersensitivity reactions tend to have early cutaneous manifestations, the progression of which is halted by early diagnosis and treatment. It is apparent that the preference for cutaneous involvement of drug hypersensitivity reactions is multi-faceted, therefore this review aims to abridge the findings from literature on the current state of the field and provide insight into the cellular and metabolic mechanisms which may contribute to severe cutaneous adverse reactions.